The Effect of Incontinence Severity on Symptom Distress, Quality of Life, and Pelvic Floor Muscle Function in Turkish Women with Urinary Incontinence - Ceren Orhan; Serap Ozgul; Emine Baran; Esra Uzelpasaci; Gulbala Nakip; Gamze Nalan Cinar; Mehmet Sinan Beksac; Turkan Akbayrak (Medical Network, 2020)
Objective: The aim of the present study was to compare the differences in symptom distress, quality of life, and pelvic floor muscle function among Turkish women with mild, moderate, or severe urinary incontinence. Study design: One hundred and twenty women with a diagnosis of urinary incontinence (54.2% stress urinary incontinence and 45.8% mixed-urinary incontinence) participated in the present study. The severity of the urinary incontinence was stratified by the Incontinence Severity Index. The Turkish versions of the Urinary Distress Inventory-6 and the Incontinence Impact Questionnaire-7 were used to assess symptom distress and quality of life, respectively. Pelvic floor muscle strength and endurance were measured using a non-invasive vaginal perineometer. Results: Symptom distress and quality of life significantly differed among the mild, moderate, and severe urinary incontinence groups (p<0.001). Patients with severe stress urinary incontinence displayed a higher decrease in quality of life than those with mild stress urinary incontinence (p<0.001). Furthermore, severe mixed urinary incontinence had a greater impact on symptom distress and quality of life compared to mild and moderate mixed urinary incontinence (p<0.05). The Incontinence Severity Index score was significantly associated with the Urinary Distress Inventory-6 and Incontinence Impact Questionnaire-7 scores (p<0.001). Conclusion: Urinary incontinence affected the symptom distress and quality of life of patients in proportion to the severity of the symptoms. Therefore, the relationship between the severity of urinary incontinence and patients' quality of life should be evaluated in clinical settings. To prevent the greater influence of incontinence on the quality of life of women with urinary incontinence, early detection of urinary incontinence and early management strategies are essential.